A new eriophyoid mite in the genus Disella from Ilex paraguariensis in Brazil - Navia, Denise; Flechtmann, Carlos H.w. (Zootaxa, 2005)
A new phytophagous mite species of Disella Newkirk & Keifer genus (Eriophyidae, Nothopodinae), namely D. ilicicola n. sp., is described from Ilex paraguariensis Saint Hilaire (Aquifoliaceae) from South Brazil. This is the second Eriophyoidea mite reported infesting I. paraguariensis in Brazil and the second Disella species described from Ilex host plants.